Substitution Mapping of a Locus Responsible for Hybrid Breakdown in Populations Derived From Interspecific Introgression Line - Munguambe, Nilsa Emilia; Inoue, Shouta; Demeter, Zita; Yamagata, Yoshiyuki; Yasui, Hideshi; Zheng, Shao-Hui; Fujita, Daisuke (Frontiers in Plant Science, 2021)
Hybrid weakness, a form of postzygotic reproductive barrier, has been reported to hinder gene flow in many crosses between wild and cultivated rice. Here, the phenomenon of hybrid weakness was observed as low tillering (i.e., low tiller number) in some progeny of an interspecific cross produced in an attempt to introduce Oryza meridionalis Ng (W1625) chromosomal segments into Oryza sativa L. ssp. japonica ‘Taichung 65’ (T65). Low-tillering lines were obtained in BC4-derived progeny from a cross between W1625 and ‘Taichung 65’ (T65), but the gene for low tillering could not be mapped in segregating populations. As a second approach to map the gene for low tillering, we analyzed an F2 population derived from a cross between the low-tillering lines and a high-yielding indica cultivar, ‘Takanari’. A major QTL for low tillering, qLTM4, was detected between PCR-based markers MS10 and RM307 on the long arm of chromosome 4, with a LOD score of 15.6. The low-tillering phenotype was associated with weak growth and pale yellow phenotype; however, low tillering plant had less reduction of grain fertility. In an F4 population (4896 plants), 563 recombinant plants were identified and the low-tillering gene was delimited to a 4.6-Mbp region between markers W1 and C5-indel3729. This region could not be further delimited because recombination is restricted in this region of qLTM4, which is near the centromere. Understanding the genetic basis of hybrid weakness, including the low-tillering habit, will be important for improving varieties in rice breeding.